(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The research investigates solar energy utilization and attitudes towards solar energy among Young Smart Farmer in eight provinces in the upper northern region of Thailand. The research employs a stratified random sampling method. 300 YSF members of the Office of Agricultural Extension and Development 6 are selected as participants through a simple random sampling technique based on the membership list. The findings reveal that out of the sampled farmers, 169 do not utilize solar energy, while 131 utilize solar energy in their agricultural practices. Most YSF possess a bachelor’s degree, with their degrees predominantly unrelated to agriculture. The participating farmers have an average agricultural experience of 7.73 years and an average age of 37.68 years. Furthermore, their average annual income amounts to 194,940 baht. The investigation demonstrates that solar energy is primarily employed for lighting and charging batteries, operating water pumps, fans, televisions, electric drills, and angle grinders. Additionally, the results indicate that farmers who utilize solar energy display more favourable attitudes towards solar energy technology than those who do not. The study identifies numerous challenges and barriers hindering the widespread adoption of solar technology, such as high costs, lack of technical knowledge, concerns regarding system maintenance, and long-term stability of solar power systems.